Landing strategies of athletes with an asymptomatic patellar tendon abnormality - Edwards, S.; Steele, J. R.; McGhee, D. E.; Beattie, S.; Purdam, C.; Cook, J. L. (Medicine & Science in Sports & Exercise, 2010)
Purpose: Risk factors associated with a clinical presentation of patellar tendinopathy are patellar tendon ultrasonographic abnormality (PTA) and excessive loading. It remains unknown whether characteristics of an athlete's landing technique contribute to this excessive patellar tendon loading. This study investigated whether asymptomatic athletes with and without PTA had different landing strategies and hypothesized that asymptomatic athletes with a PTA would create higher patellar tendon loading and a different lower-limb landing strategy compared with athletes with normal patellar tendons.